Characterization of SARS-CoV-2 variants associated with reinfection cases in Botucatu, Brazil: a comparative genomic study - A. M. S. Kubo; R. A. Silveira; D. B. S. Figueiredo; L. A. Umezawa; K. I. Tasca; C. M. C. B. Fortaleza; G. T. Valente; R. M. T. Grotto (Brazilian Journal of Biology)
Abstract The global spread of SARS-CoV-2 triggered the COVID-19 pandemic, resulting in a significant number of deaths. Variants such as B.1.1.7, B.1.351, P.1, and BA.1 distinguished by spike protein mutations arose due to immune pressure and lack of repair mechanisms. These changes amplified infectivity, increasing the chances of reinfection. We retrospectively included patients who have two positive tests for SARS-CoV-2 detected by real-time reverse transcription polymerase chain reaction with an interval of 90 days, or more, between 01 March 2020 and 30 April 2022. SARS-CoV-2 whole genome sequencing was performed for both infections, and the variants were identified using the Phylogenetic Assignment of Named Global Outbreak Lineages (Pangolin) database. This study identified a total of 254 cases of reinfections, 50.8% of the cases caused by the P.1 and BA.1 variants. Compared to the state scenario, a lower detection of the B.1.617.2 variant was identified, highlighting the importance of mass vaccination in the city of Botucatu, Brazil. However, most second infections (98.8%) were identified during the BA.1 wave, showing the effect of viral adaptative mechanisms on infection dynamics even in a vaccinated population. Taken together, our results emphasize the importance of constant monitoring and the maintenance of COVID-19 prevention and control strategies.